1999
DOI: 10.1007/s004290050294
|View full text |Cite
|
Sign up to set email alerts
|

Sodium transport-related proteins in the mammalian distal nephron - distribution, ontogeny and functional aspects

Abstract: The mammalian distal nephron plays a pivotal role in adjusting urinary sodium excretion. Successive portions of the renal tubule are formed to adapt to this function, and an axial heterogeneity of the distal segments has been defined. The specific transport properties of these epithelia are accomplished by the expression of proteins (cotransporters, exchangers, channels) governing the movement of ions on either cell side. Molecular cloning of these proteins has had a marked impact on the study of their localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 201 publications
(282 reference statements)
1
64
0
1
Order By: Relevance
“…As the experiments were performed on principal cells from the open-end portion of the collecting duct fragments, where the single epithelial layer 16 Ilyaskin et al of cells was well-stirred, the simple "symmetrical" model could be used. The set of membrane osmolyte carriers and transporters taken into account in the model was chosen according to expression patterns in collecting duct cells Palmer 1987, 1989;Duc et al 1994;Bachmann et al 1999;Feraille and Doucet 2001;Muto 2001;Najjar et al 2005;Pisitkun et al 2006;Chou et al 2008;Uawithya et al 2008;Wakamatsu et al 2009). The transport of osmolytes and water depended on the area of the cell surface A, which was assumed to be constant and independent of cellular volume because of the low extensibility of the lipid bilayer.…”
Section: Methods Of Mathematical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…As the experiments were performed on principal cells from the open-end portion of the collecting duct fragments, where the single epithelial layer 16 Ilyaskin et al of cells was well-stirred, the simple "symmetrical" model could be used. The set of membrane osmolyte carriers and transporters taken into account in the model was chosen according to expression patterns in collecting duct cells Palmer 1987, 1989;Duc et al 1994;Bachmann et al 1999;Feraille and Doucet 2001;Muto 2001;Najjar et al 2005;Pisitkun et al 2006;Chou et al 2008;Uawithya et al 2008;Wakamatsu et al 2009). The transport of osmolytes and water depended on the area of the cell surface A, which was assumed to be constant and independent of cellular volume because of the low extensibility of the lipid bilayer.…”
Section: Methods Of Mathematical Modelingmentioning
confidence: 99%
“…There are multiple different pathways involved in the transport of solutes across the cell plasma membrane. Ion transport across principal cells is mediated by sodium (Duc et al 1994;Bachmann et al 1999;Loffing and Kaissling 2003;Frindt et al 2007), potassium (Frindt and Palmer 1987;Frindt and Palmer 1989;Muto 2001;Najjar et al 2005) and chloride (Sansom et al 1990;Todd-Turla et al 1996) channels, Na/K-pumps (Feraille and Doucet 2001;Wetzel and Sweadner 2001) and several types of ion transporters (Kuwahara et al 1991;Chou et al 2008). It is thus important to quantify the relative contribution of the various transporting mechanisms to the net transmembrane ion flux in order to understand the mechanism of the maintenance of the water-electrolyte balance in a principal cell.…”
Section: Introductionmentioning
confidence: 99%
“…Antibody to calbindin, showing the signal beginning with the terminal DCT (DCT2 in rats; for review see Bachmann et al 1999; data not shown) and continuing to the transition of the CNT to the collecting duct (Fig. 3A-D), showed an overlap with anti-hepcidin as revealed by double-staining in the rat and the mouse using both Nand C-terminal antibodies.…”
Section: Localizationmentioning
confidence: 97%
“…Confluent mpkCCD cl4 cells grown on Transwell filters (24-mm diameter) were transferred for 3 h to HEPES-buffered Dulbecco's modified Eagle's medium and kept under air atmosphere at 37°C. The cell layers were then permeabilized apically to monovalent ions with 35 g/ml amphotericin B for 15 min at 37°C in Na ϩ -free buffer containing 116 mM K ϩ gluconate, 1.8 mM CaCl 2 , 1.6 mM MgCl 2 , 0.8 mM KH 2 PO 4 , 2 mM D-glucose, 12 mM essential amino acids, 2 mM nonessential amino acids, 0.4 mM glutamine, 25 mM HEPES, 3 mM Ba(OH) 2 and adjusted to pH 7.4 with Tris. The filters were then transferred to a Ussing chamber, and Na ϩ was added to the desired final concentration by mixing Na ϩ buffer (Naϩ replacement of K ϩ ) with the Na ϩ -free buffer.…”
Section: Rbmentioning
confidence: 99%
“…It displays a potent Na ϩ retaining action at the level of tight epithelia, in particular in the aldosterone-sensitive distal nephron (ASDN), 1 a portion of the kidney tubule that extends from the second part of the distal convoluted tubule to the medullary collecting duct (2)(3)(4). The segment-specific cells of the ASDN express a transcellular pathway for Na ϩ reabsorption that is composed of the luminal epithelial Na ϩ channel (ENaC) and the basolateral Na,KATPase (Na ϩ pump).…”
mentioning
confidence: 99%